2016
DOI: 10.1073/pnas.1524390113
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco mosaic virus-directed reprogramming of auxin/indole acetic acid protein transcriptional responses enhances virus phloem loading

Abstract: Vascular phloem loading has long been recognized as an essential step in the establishment of a systemic virus infection. In this study, an interaction between the replication protein of tobacco mosaic virus (TMV) and phloem-specific auxin/indole acetic acid (Aux/IAA) transcriptional regulators was found to modulate virus phloem loading in an age-dependent manner. Promoter expression studies show that in mature tissues TMV 126/183-kDa-interacting Aux/IAAs predominantly express and accumulate within the nuclei … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
56
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 100 publications
(121 reference statements)
1
56
0
Order By: Relevance
“…They suggest 440 that nuclear association of plant RNA virus components can manipulate transcriptional 441 regulation and re-programme gene expression in vascular tissue and that this may be a more 442 general strategy used by plant viruses to facilitate long-distance movement than previously 443 supposed (Solovyev and Savenkov, 2014;Collum et al, 2016 NbHIPP26 would result in increased spread of infection and not inhibition as we observed.…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…They suggest 440 that nuclear association of plant RNA virus components can manipulate transcriptional 441 regulation and re-programme gene expression in vascular tissue and that this may be a more 442 general strategy used by plant viruses to facilitate long-distance movement than previously 443 supposed (Solovyev and Savenkov, 2014;Collum et al, 2016 NbHIPP26 would result in increased spread of infection and not inhibition as we observed.…”
mentioning
confidence: 69%
“…The eukaryotic cell nucleolus contains the factors needed for its main function in ribosome 422 subunit production, and this is where ribosomal RNA transcription, processing, and and spread in the phloem of older leaves (Collum et al, 2016).…”
mentioning
confidence: 99%
“…Previous studies have reported that plant viruses can hijack the auxin signalling pathway to promote virus infection and virus movement in the host plants (Collum et al., ; Jin et al., ). The capsid protein of Rice dwarf virus (RDV) interferes with auxin signalling by binding to the rice AUX/IAA protein OsIAA10, thereby protecting it from degradation by the 26S proteasome and resulting in typical RDV symptoms in infected plants (Jin et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…These transcriptional repressors have been suggested to regulate genes involved in phloem loading. TMV infection inhibits the nuclear localization of AUX/IAA proteins, resulting in the transcriptional reprogramming of mature vascular tissue, which is correlated with enhanced TMV spread in the phloem of older leaves (Collum et al., ). Taken together, these data are consistent with our findings showing that BNYVV P25 interacts with BvAUX28, presumably inactivating its function as a transcriptional repressor through the disruption of its nuclear localization.…”
Section: Discussionmentioning
confidence: 99%
“…The TMV replicase complex also interacts with a specific auxin/indole acetic acid (Aux/IAA) host transcriptional regulator. This interaction disrupts the control of host genes implicated in virus movement, plasmodesmata gating and defence in the companion cells, enhancing TMV phloem loading (Padmanabhan et al, 2008;Collum et al, 2016).…”
Section: Effects Of Tmv Replicase Proteinmentioning
confidence: 99%